Efektivitas Implementasi Ronde Keperawatan terhadap Kualitas Asuhan Keperawatan dan Kepuasan Kerja Perawat di Ruang Rawat Inap Rumah Sakit: Literatur Review - Lincariah Purba; Asnet Leo Bunga (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Nursing rounds are a nursing management strategy aimed at improving the quality of nursing care through structured clinical communication, continuous evaluation, and active nurse involvement in clinical decision-making. Previous studies have reported that the implementation of nursing rounds can enhance nursing performance, patient safety, and nurses’ job satisfaction; however, research findings remain inconsistent.This literature review aimed to analyze the effectiveness of nursing round implementation on the quality of nursing care and nurses’ job satisfaction. MethodsThis study employed a literature review design by analyzing 20 national and international journal articles published between 2020 and 2025. Articles were retrieved from Google Scholar, PubMed, ProQuest, and ScienceDirect using keywords related to nursing rounds, quality of nursing care, and nurses’ job satisfaction. Article selection followed inclusion and exclusion criteria and adhered to PRISMA guidelines.The synthesis revealed that nursing round implementation was generally effective in improving the quality of nursing care, as indicated by enhanced nursing performance, patient safety, and continuity of care. In addition, most studies reported an improvement in nurses’ job satisfaction, particularly in terms of professionalism, practice autonomy, and teamwork. Nevertheless, several observational studies reported non- significant effects on certain clinical outcomes, which were influenced by study design variations and implementation quality.The implementation of nursing rounds is effective in improving the quality of nursing care and nurses’ job satisfaction when conducted in a structured and consistent manner with adequate managerial support. Nursing rounds are recommended as an evidence-based strategy to improve nursing service quality in hospital settings.